TOD (TRANSIT ORIENTED DEVELOPMENT) INDEX STUDY ON VALUE CREATION: CASE STUDY OF THE TOD AREA IN JAKARTA - Arliani, Vani
TOD (Transit Oriented Development) is an integrated transportation planning concept with land use, which is generally centered on a transit point. Transit node areas are places that allow transportation users to move spatially easily to other areas, accompanied by the ease of changing between modes. This shows that the transit node area has a good level of external accessibility. The land use function for the area around the transit node area generally has various types of land use with medium to dense density levels. Therefore, in TOD areas, a transportation network and facilities plan is needed to improve internal accessibility in the form of special pedestrian areas and special bicycle lanes. This is in line with the TOD design concept which focuses on sustainable design that is environmentally friendly. Technically, TOD describes a strong inter-relationship between accessibility and various land uses, so this research will assess TOD based on three factors, namely external accessibility, internal accessibility and land use. TOD was built with the aim of maximizing the use of space with a variety of land uses and improving the quality of life (lifability) where holistic infrastructure is available to fulfill various activities in a transit area as well as the creation of a wider open space area. By applying TOD, it will be possible to minimize the movement of people because all activities can be fulfilled at a transit node. Empirically, it is very rare to find an area that is designed according to the ideal TOD criteria parameters. This is because the TOD concept was born after many transit locations had been formed evolutionarily, so that there was not a single area that was truly in accordance with the theoretical technical aspects of TOD. Referring to the goals and benefits of TOD, a classification process is needed to assess the level of fulfillment of an area to become an ideal TOD. Several previous studies carried out TOD classification using typology, which is a systematic grouping system, but it has the weakness of not being able to measure it quantitatively so it cannot know the output. It is important to carry out quantitative assessments in order to optimize the planning of a TOD area to become an ideal TOD, as well as to determine the impacts and opportunities it creates. In this research, a TOD measurement system with an index method was developed, which can quantitatively analyze various different criteria in a single unit. Weight calculations for index calculations are carried out using the AHP (Analytical Hierarchy Process) method because it can measure complex problems qualitatively and quantitatively using pairwise comparisons. Creating a level of fulfillment in an area that is assessed based on TOD criteria will produce output in the form of open opportunities for utilization (value creation). Value creation is a phenomenon to obtain an increase in price or more value from a condition so that it is more efficient. The most visible value creation is from increasing land prices or land rental prices. It is quite difficult to calculate the value creation of land that is close together but has a different number of floors. So value creation in this research is calculated based on the addition of the total value of assets built in a TOD area, not just from changes in land value or rental value alone. This research hypothesis puts forward the association between the TOD index which shows the level of TOD fulfillment in an area and value creation. As well as the second hypothesis, there is an association between the components that form the index, namely internal accessibility to value creation. The research location was carried out in one of the metropolitan cities in Indonesia, namely Jakarta with six research locations, namely the areas namely Lebak Bulus, Dukuh Atas, Kelapa Gading, Pasar Senen, Tanah Abang and Manggarai. The research respondents obtained were 407 respondents, whereas previously 23 different respondents were obtained for the pilot survey. The results of research in several TOD areas with the same radius show a positive relationship between the TOD index and value creation. The greater the fulfillment of the ideal TOD criteria (the higher the TOD index), the greater the value creation that will be formed. The correlation formed is an exponential correlation. An assessment of one of the components forming the index, namely internal accessibility, shows that internal accessibility has the greatest influence on the value creation value formed in the TOD area, where the coefficient of determination of internal accessibility is higher than external accessibility or the TOD index on value creation.